The future of code mixing research: Integrating psycholinguistic and formal grammatical theories*. Issue 5 (22nd March 2016) - GOLDRICK, MATTHEW; PUTNAM, MICHAEL; SCHWARZ, LARA
Abstract : Our keynote article "Coactivation in bilingual grammars: A computational account of code mixing" (Goldrick, Putnam & Schwarz) aimed to provide a framework that would begin to unify psycholinguistic and formal grammatical approaches to code mixing. We situated our account within a large body of psycholinguistic and phonetic evidence suggesting that, under many conditions, multiple representational elements simultaneously occupy (to varying degrees) a single position within a linguistic structure. The presence of such blends in multilingual cognition is not compatible with many formal grammatical approaches that assume mental representations are necessarily discrete.